Dear Hanna : a novel - Stage, Zoje (Thomas & Mercer, 2024)
Hanna is no stranger to dark thoughts: as a young child, she tried to murder her own mother. But that was more than sixteen years ago. And extensive therapy--and writing letters to her younger brother--has since curbed those nasty tendencies. Now twenty-four, Hanna is living an outwardly normal life of domestic content. Married to real estate agent Jacob, she's also stepmother to his teenage daughter Joelle. They live in a beautiful home, and Hanna loves her career as a phlebotomist--a job perfectly suited to her occasional need to hurt people. But when Joelle begins to change in ways that don't suit Hanna's purposes, her carefully planned existence threatens to come apart. With life slipping out of her control, Hanna reverts to old habits, determined to manipulate the events and people around her. And the only thing worse than a baby sociopath is a fully grown one.